2010
DOI: 10.3892/ijmm.2010.550
|View full text |Cite
|
Sign up to set email alerts
|

Influence of LPS, TNF, TGF-�1 and IL-4 on the expression of MMPs, TIMPs and selected cytokines in rat synovial membranes incubated in vitro

Abstract: Abstract. Synovial membranes are formed by four main types of cells, i.e. fibroblasts, macrophages, epitheliocytes and adipocytes. To study the combined effect of various factors on these cell populations, synovial membranes dissected from rat knee joints were incubated in control medium or medium with lipopolysaccharide (LPS), TNF, TGF-ß1 or IL-4 for 12 h. LPS stimulated TNF secretion and both agents stimulated secretion of IL-6. TGF-ß1 slightly increased IL-6 secretion. LPS increased the mRNA levels of IL-6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 100 publications
2
9
2
Order By: Relevance
“…Some of the gene changes in response to TGFβ have previously been reported in other cell types. For example TGFβ is reported to regulate ADAM12 [54], ADAMTS1 [55], ADAMTS4 [56,57], ADAMTS16 [58], TIMP3 [59], TIMP4 [60], thrombospondin [61], aggrecan [62], collagen and fibronectin [63]. These responses are analogous to those seen in our model with TGFβ and strain, further supporting our conclusion that TGFβ plays a key role in the strain regulation of most metalloproteinase genes.…”
Section: Discussionsupporting
confidence: 87%
“…Some of the gene changes in response to TGFβ have previously been reported in other cell types. For example TGFβ is reported to regulate ADAM12 [54], ADAMTS1 [55], ADAMTS4 [56,57], ADAMTS16 [58], TIMP3 [59], TIMP4 [60], thrombospondin [61], aggrecan [62], collagen and fibronectin [63]. These responses are analogous to those seen in our model with TGFβ and strain, further supporting our conclusion that TGFβ plays a key role in the strain regulation of most metalloproteinase genes.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, our expression data is corroborated by studies of LPS-treated human-derived monocytes, in which increased levels of MMP9, MMP10, MMP14, and decreased levels of TIMP-2 were reported [15]. LPS treatment of isolated tissues, containing a mixed cell population including macrophages, also leads to increased MMP and decreased TIMP2 RNA expression levels [18]. Interestingly, the latter study also reported altered expression of genes that were not affected by LPS treatment of RAW 264.7 cells in the current study.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that inflammatory cytokines induce MMPs, which may be a pivotal role for inflammatory cytokines such as IL-6 and IL-8 in the pathogenesis of diseases such as rheumatoid arthritis [25], chronic obstructive pulmonary disease [26], and corneal ulceration [27]. We showed that IL-6, IL-8 and MMP-1were produced by LPS in nasal polyp-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 60%